NIGCOMSAT-1R SATELLITE-BASED AUGMENTATION SYSTEM(SBAS) TEST BED TRIAL - Lawal, Lasisi Salami; Chatwin, Chris; Li , Dongjun (IJRDO - Journal of Electrical And Electronics Engineering, 2020)
In October, 2016 China Great Wall Industry Corporation and Spacestar Technology Company Ltd of China entered into cooperative agreement with Nigerian Communications Satellite Ltd on a Satellite-Based Augmentation System (SBAS) performance test and assessment of the Nigerian Communications Satellite (NIGCOMSAT-1R) augmentation System exploiting NIGCOMSAT-1R L Band. This paper examines test bed experimentation conducted in conjunction with partners to validate functional requirements, performance validation of units, sub-systems and systems of both the SBAS payload and ground infrastructure before a pilot project demonstration of capabilities and proof-of-concept nationwide and extension to parts and regions of Africa.